Sleep problems are related to commuting accidents rather than to workplace accidents - Vargas-Garrido, Héctor (BMC Public Health, 2021)
BACKGROUND: This study aimed to verify the relationships between sleep problems and both commuting and workplace accidents in workers of both sexes. METHODS: The study was carried out with a sample of workers (n = 2993; 50.2% female) from the Chilean Quality of Life Survey (ENCAVI) 2015–2016, while the rates of both workplace and commuting accidents were extracted from the statistics of the Superintendence of Social Security (SUSESO 2015; 180,036 and 52,629 lost-time accidents, respectively). RESULTS: Chilean workers sleep less than the rest of the people in the country (M(W) = 7.14 vs. M(O) = 7.33; t (6789) = − 5.19; p < .001), while the Chilean people as a whole sleep less compared to those of other countries (7.24 h per day). Likewise, it was found that sleep problems are more strongly related to commuting than to workplace accidents. In this vein, sleep quantity can explain 24% of the variance in commuting accidents’ rates (Stepwise Method; R(2) = .30, F (1.14) = 5.49, p < .05; β = −.55, p < .05), by using aggregated data with all types of commuting roles (driver of a vehicle, a passenger of public or private transport, or as a pedestrian). CONCLUSIONS: Our findings show that sleep quantity has a more robust relationship with commuting than workplace accidents, a neglected issue so far. Future prevention programs should emphasize sleep hygiene and focus on commuting to and from work. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10737-5.